2020
DOI: 10.1002/advs.202002589
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Surface Modification Technologies in Nanomedicine for Deep Tumor Penetration

Abstract: The impermeable barrier of solid tumors due to the complexity of their components limits the treatment effect of nanomedicine and hinders its clinical translation. Several methods are available to increase the penetrability of nanomedicine, yet they are too complex to be effective, operational, or practical. Surface modification employs the characteristics of direct contact between multiphase surfaces to achieve the most direct and efficient penetration of solid tumors. Furthermore, their simple operation make… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
88
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 149 publications
(88 citation statements)
references
References 178 publications
(184 reference statements)
0
88
0
Order By: Relevance
“…However, BPNS could easily react with oxygen and water, subsequently degrade in air-exposed water solution [ 27 ]. Thus, surface covalent or noncovalent modification with small molecules were reportedly capable of stabilizing BPNS [ 28 , 29 ]. In a recent study, Ag + was observed to stabilize BPNS in air and realize the delivery of metal ion in one strategy.…”
Section: Introductionmentioning
confidence: 99%
“…However, BPNS could easily react with oxygen and water, subsequently degrade in air-exposed water solution [ 27 ]. Thus, surface covalent or noncovalent modification with small molecules were reportedly capable of stabilizing BPNS [ 28 , 29 ]. In a recent study, Ag + was observed to stabilize BPNS in air and realize the delivery of metal ion in one strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, non-enzyme molecules-based functionalization of nanocarriers’ surfaces has been reported which can also cause TME damage, leading to deeper nanomedicine penetration. Fluorinated chitosan was used by Li et al for the construction of a nanosystem that enhanced deep penetration via the conjectural function of transiently opening tight junctions between cells (Li et al, 2020 ). Fortunately, virus-derived junction opener protein also can transiently open intercellular junctions in epithelial tumors by causing the cleavage in protein desmoglein-2, and can also be used in surface modification for tumor penetration (Wang et al, 2018 ).…”
Section: Surface Modification Strategies For Deeper Penetration To Tumorsmentioning
confidence: 99%
“…Beyond an increase in size [ 30 ] or a change in nanoparticle charge, [ 31 ] shape [ 32 ] has also been identified as a key factor that influences nanoparticle biological responses. For example, relative to spherical particles, disk‐like particles can persist in circulation and enable higher targeting but are less easily endocytosed, [ 33 ] needle‐like nanoparticles could induce endothelial cell membrane disruption and thus increase drug penetration into cells, [ 34 ] elongated particles can exhibit higher adhesion in the in vitro microvascular network, [ 35 ] rod‐like nanoparticles (mimicking bacteria) more readily attach to cell surfaces, [ 36 ] oblate ellipsoid particles (mimicking platelets) have longer‐lasting interactions with receptors, [ 37 ] and needle‐like nanoparticles with tip dimensions of ≈100 nm facilitate higher cytoplasmic delivery rates.…”
Section: Introductionmentioning
confidence: 99%